Energy Harvesting From Floor Integrated Piezoelectric Sensor - Çavuş, Birol; Oy, Sibel Akkaya (Fırat University, 2024)
This study introduces an experimental energy harvesting system based on ground-mounted piezoelectric ceramic transducers for low-power applications where human mobility is high. The voltage that only a PZT can produce is not at a level that can energize a system alone. Therefore, the total power to be obtained has been increased by connecting PZTs in series and parallel with the appropriate circuit topology that can maximize the harvested power. In the experimental study, 5 PZTs were placed on each short side of a 20 × 30 cm wooden floor, and energy was harvested from 10 PZTs in total with 10 voltage doublers. Individuals of four different weights stepped on the experimental setup for one minute at three different walking speeds and all results were obtained graphically. A 220 K? resistor is used as load. When the experimental setup was tested with an individual weighing 48 kg, a maximum power 23.42 ?W (2.27 volts), 13.13 ?W (1.70 volts) for 58 kg, 59.56 ?W (3.62 volts) for 71 kg and 55.68 ?W (3.50 volts) for 85 kg was harvested. Experimental results have shown that as the walking speed of the same individual increases, the average tension to be obtained increases, and the heavier individuals at the same walking speeds provide more energy harvest.

Bu çalışma insan hareketliliğinin fazla olduğu yerlerde, düşük güçlü uygulamalar için zemine yerleştirilen piezoelektrik seramik dönüştürücülere dayalı deneysel bir enerji hasat sistemini tanıtmaktadır. Yalnızca bir PZT’nin üretebildiği gerilim tek başına bir sisteme enerji verebilecek seviyede değildir. Bu yüzden PZT’ler hasat edilen gücü en üst seviyeye çıkarabilecek uygun devre topolojisiyle seri ve paralel bağlanarak elde edilecek toplam güç arttırılmıştır. Deneysel çalışmada 20 × 30 cm’lik ahşap bir zeminin her bir kısa kenarına 5 adet PZT yerleştirilmiş, toplamda 10 adet PZT’den 10 adet gerilim ikileyici ile enerji hasadı yapılmıştır. Dört farklı ağırlıkta birey üç farklı yürüme hızında bir dakika boyunca deney düzeneğine basmış ve tüm sonuçlar grafiksel olarak elde edilmiştir. Yük olarak 220 K? direnç kullanılmıştır. Deney düzeneği 48 kg ağırlığındaki bireyle test edildiğinde maksimum 23,42 ?W (2,27 volt), 58 kg ağırlığında 13,13 ?W (1,70 volt), 71 kg ağırlığında 59,56 ?W (3,62 volt), 85 kg ağırlığında 55,68 ?W (3,50 volt) gerilim hasat edilmiştir. Deneysel sonuçlar aynı bireyin yürüme hızı arttıkça elde edilecek ortalama gerilimin yükseldiğini, ayrıca aynı yürüme hızlarındaki bireylerden ağır olanın daha fazla enerji hasat edilmesini sağladığını göstermiştir.
Zemine Entegre Piezoelektrik Sensörden Enerji Hasadı
Keywords: Engineering; Mühendislik